The Role of Metaphor and the Role of a Creative Person in Constructing a Conceptual Picture of the World (Indian Journal of Social Science and Literature (IJSSL), 2024)
The article is devoted to such concepts as a linguistic personality, a linguistic picture of the world, the national and cultural specificity of a linguistic personality and a conceptual picture of the world. All these concepts are central concepts within the anthropocentric approach to the study of metaphor. It also discusses some features of the use and functioning of metaphor in poetic works in the linguacultural aspect, as well as the role of a creative person in constructing a conceptual picture of the world.